WHATSAPP APPLICATION AS A DIGITAL COMMUNICATION TOOL IN TEACHING AND LEARNING ENGLISH IN AN INDONESIAN JUNIOR HIGH SCHOOL - Sitti Rahmawati Rau; Baso Jabu; Munir Munir (Universitas Negeri Makassar, 2022)
The purpose of this study was to find out how the teacher implement the WhatsApp application as a digital communication tool for learning English in junior high school and its impact on students. This study used a qualitative descriptive method and was conducted in Pangkep Junior High School, South Sulawesi, as many as 21 students from class VIII C and 1 English teacher were selected as research subjects through random sampling techniques. Data was obtained from Observation, Interviews, and Documentation. The results obtained from the data analysis are 1) The implementation of the teacher when using the WhatsApp application with 3 indicators as preparation for creating a WhatsApp group, implementation, namely sending file materials, and evaluation, namely providing evaluations and assignments to students. 2) the impact on students by learning to use the WhatsApp application, namely the positive impact: which is being able to do assignments anywhere, easy to understand the material given, the negative impact: which is being unable to ask questions directly, and interact with students is less established.